2014
DOI: 10.1007/s10815-014-0194-3
|View full text |Cite
|
Sign up to set email alerts
|

Which isolated sperm abnormality is most related to sperm DNA damage in men presenting for infertility evaluation

Abstract: Background Sperm DNA damage is common in infertile men and is associated with poor semen parameters but the impact of an isolated sperm abnormality on sperm DNA damage has not been studied. Objective To evaluate sperm DNA damage in a large cohort of infertile men with isolated sperm defects. Design, setting and participants Retrospective study of 1084 consecutive, non-azoospermic infertile men with an isolated sperm defect: isolated oligozoospermia (iOligo), isolated asthenozoospermia (iAstheno) or isolated te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 65 publications
6
23
1
Order By: Relevance
“…Several investigators observed lower sDNAfrag in men with higher sperm concentration, total motility, progressive motility and normal morphology (Belloc et al, 2014;Moskovtsev et al, 2009;Oosterhuis et al, 2000;Shen et al, 2002;Zhang et al, 2008), whereas others showed that these parameters are not correlated with sDNAfrag (Ricci et al, 2002). However, after use of sperm-preparation techniques, results appear more consistent, several reports finding that after swim-up the percentage of sDNAfrag was negatively correlated with motility and morphology (Lopes et al, 1998;Sharbatoghli et al, 2012), with the same results observed after the use of DGC (Sakkas et al, 1999).…”
Section: Tunel+ H-tunel+ Tunel+ H-tunel+ Concentrationmentioning
confidence: 85%
See 1 more Smart Citation
“…Several investigators observed lower sDNAfrag in men with higher sperm concentration, total motility, progressive motility and normal morphology (Belloc et al, 2014;Moskovtsev et al, 2009;Oosterhuis et al, 2000;Shen et al, 2002;Zhang et al, 2008), whereas others showed that these parameters are not correlated with sDNAfrag (Ricci et al, 2002). However, after use of sperm-preparation techniques, results appear more consistent, several reports finding that after swim-up the percentage of sDNAfrag was negatively correlated with motility and morphology (Lopes et al, 1998;Sharbatoghli et al, 2012), with the same results observed after the use of DGC (Sakkas et al, 1999).…”
Section: Tunel+ H-tunel+ Tunel+ H-tunel+ Concentrationmentioning
confidence: 85%
“…This damage can then affect oocyte activation after fertilization (Gannon et al, 2014). Various putative causes of sperm DNA fragmentation (sDNAfrag) have been discussed: apoptosis, abortive spermatogenesis, genetic factors, meiosis and spermiogenesis defects, and oxidative stress (Belloc et al, 2014;Benkhalifa et al, 2014). Whatever the origin, the detrimental effects of increased rates of sDNAfrag on male fertility have been clearly described (Sakkas and Alvarez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with many studies reporting a positive correlation between increasing male age and sperm DNA damage (Moskovtsev, Willis, & Mullen, ; Ramasamy et al, ; Sharma et al, ; Zitzmann, ) doubling from 25 to 55 years of age (Spanò et al, ). Indeed, APA could cause sperm DNA fragmentation (Agarwal, Makker, & Sharm, ; Belloc, Benkhalifa, Cohen‐Bacrie, Dalleac, Chahine, et al, ; Johnson et al, ; Nijs et al, ; Singh, Muller, & Berger, ; Wyrobek et al, ) and chromatin decondensation (Belloc et al, ; Nijs et al, ; Wyrobek et al, ). Moreover, there is relative linear correlation between APA and sperm aneuploidy rate (Agarwal et al, ; Sloter, Nath, Eskenazi, & Wyrobek, ; Sloter, Marchetti, et al, ; Wyrobek et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The last two decades many studies highlighted the importance of male fertility declining and spermatogenesis clock dysregulation (Skakkebaek et al, ). However, until today there is a lack of consensus concerning APA contribution on sperm parameters (Alshahrani et al, ; Andolz, Bielsa, & Vila, ; Fisch, Goluboff, & Olson, ; Kidd, Eskenazi, & Wyrobek, ), sperm DNA integrity (Belloc, Benkhalifa, Cohen‐Bacrie, Dalleac, Chahine, et al, ; Sartorelli, Mazzucatto, & de Pina‐Neto, ; Singh, Muller, & Berger, ; Sharma et al, ; Stone, Alex, Werlin, & Marrs, ), embryo development, clinical outcomes (Dain, Auslander, & Dirnfeld, ; Ferreira, Braga, Bonetti, Pasqualotto, & Iaconelli, ; Mathieu, Ecochard, & Bied, ) genetic and epigenetic state of fetus (Jyothy, Kumar, & Mallikarjuna, ), and/or of offspring (Sharma et al, ). It seems important to elucidate the risks to develop epigenetic diseases with paternal origin including autism and schizophrenia (Gingrich, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation